2018
DOI: 10.1111/apha.13171
|View full text |Cite
|
Sign up to set email alerts
|

Perivascular adipose tissue: A new possible tissue augmenting coronary vasodilatation in response to acute hypoxia

Abstract: Ralevic, V. 2018. Coronary artery hypoxic vasorelaxation is augmented by perivascular adipose tissue through a mechanism involving hydrogen sulphide and cystathionine -β synthase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
(30 reference statements)
0
2
0
Order By: Relevance
“…Coronary perivascular adipose tissue has been reported to weaken endothelium‐dependent vasodilation by modulating K + channel activity and potentiate coronary artery contraction . Recently, it has been demonstrated that hydrogen sulphide (H 2 S) released from the perivascular adipose tissue augments coronary vasodilation in response to acute hypoxia . These observations extend the previously recognized role of H 2 S as an oxygen sensor and transducer of hypoxia to the myocardial vasculature and move the H 2 S synthesizing enzyme cystathionine β‐synthase (CBS) into focus as a candidate target for the treatment of heart failure …”
mentioning
confidence: 87%
“…Coronary perivascular adipose tissue has been reported to weaken endothelium‐dependent vasodilation by modulating K + channel activity and potentiate coronary artery contraction . Recently, it has been demonstrated that hydrogen sulphide (H 2 S) released from the perivascular adipose tissue augments coronary vasodilation in response to acute hypoxia . These observations extend the previously recognized role of H 2 S as an oxygen sensor and transducer of hypoxia to the myocardial vasculature and move the H 2 S synthesizing enzyme cystathionine β‐synthase (CBS) into focus as a candidate target for the treatment of heart failure …”
mentioning
confidence: 87%
“…This generates a latent cellular state of restricted energy production which may suddenly and unexpectedly progress to organ failure if substrate supply is further decreased (eg, because of a temporary heart insufficiency) or an extreme organ performance is demanded (eg, because of high muscle workload, intake of new drugs, long-term starvation or an infectious disease). 2,3 It is necessary to decipher the molecular mechanisms underlying disease-related metabolic changes at the cellular level to understand how malfunctions of tissues, organs and organisms develop. This will also help to develop efficient medical strategies to prevent or delay the disease manifestation and to improve recovery of the affected organ.…”
mentioning
confidence: 99%